Psychological Capital on College Teachers’ and Students’ Entrepreneurial Performance and Sports Morality Under Social and Political Education - Lyu, Tao; Tang, Lijun; Yang, Zeyun (Frontiers in Psychology, 2022)
The aim is to improve the Entrepreneurial Performance (EP) and sports morality of College Teacher-and-Student Entrepreneurs (College Entrepreneurs). Consequently, Psychological Capital (PsyCap) is creatively combined with Social and Political Education (SPE) to explore College Entrepreneurs' EP and sports morality. Firstly, following a theoretical model implementation, this paper proposes several hypotheses. Then, a Questionnaire Survey (QS) is designed, and the data are analyzed. The results show that (1) Gender has little impact on EP and sports morality; (2) PsyCap significantly affects the EP of College Entrepreneurs at the age of 33-38; (3) In terms of educational background, average scores of PsyCap+SPE of bachelors are the highest, followed by masters or above, and finally, the college undergraduate; (4) The average score of PsyCap+SPE of married respondents is 4.0, while that of the unmarried is 3.7; (5) There is a significant difference between College Entrepreneurs' EP under the dimension of basic enterprise situation; (6) the average score of the length of entrepreneurship is 9.87, which has the most significant impact on the EP and sports morality, and the significance of sports morality is 0.04. Among them, the most significant impact on EP and sports morality is weekly sports participation, with a score of 9.67. Therefore, PsyCap+SPE plays a positive role in the EP of College Entrepreneurs. By contrast, sports morality has little impact on EP. The study provides a reference for the research on the influence of entrepreneurship and sports morality of College Entrepreneurs.